Outsourcing: Role, Characteristics and Directions of the Application - Harizanova, Margarita (Research Papers, 2012)
The study is devoted to the outsourcing and the new management approach that is applied very often in the practice of the organizations. The author analyses the prerequisites for spreading the outsourcing.The international division of labour and the cluster organization are the foundation for the arise and its development. All business processes and production are embraced by the outsourcing. The choice of this approach of the organization management depends on a lot of purposes which are carefully analyzed in the study.